2017
DOI: 10.3389/fmicb.2017.01234
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Umbelliferone Reduces Ralstonia solanacearum Biofilm Formation, Transcription of Type III Secretion System Regulators and Effectors and Virulence on Tobacco

Abstract: Ralstonia solanacearum is one of the most devastating phytopathogens and causes bacterial wilt, which leads to severe economic loss due to its worldwide distribution and broad host range. Certain plant-derived compounds (PDCs) can impair bacterial virulence by suppressing pathogenic factors of R. solanacearum. However, the inhibitory mechanisms of PDCs in bacterial virulence remain largely unknown. In this study, we screened a library of coumarins and derivatives, natural PDCs with fused benzene and α-pyrone r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 57 publications
4
31
0
Order By: Relevance
“…prhO deletion did not alter the expression of prhJ , phcA and prhN , which are known to be important for the expression of hrpG and prhG (Hikichi et al ., ; Zhang et al ., ), indicating that the regulation of PrhO on the expression of hrpG and prhG is independent of these known regulating pathways. Recently, we have identified a plant‐derived compound, umbelliferone, which impairs T3SS expression via HrpG and PrhG, but independent of these known regulators (Yang et al ., ), supporting our speculation that certain novel pathways should be integrated for the expression of hrpG and prhG in R. solanacearum . It should be noted that HrpB is not expressed until contact with hrp ‐inducing medium or with host plants, whereas HrpG is best expressed in rich medium.…”
Section: Discussionsupporting
confidence: 86%
“…prhO deletion did not alter the expression of prhJ , phcA and prhN , which are known to be important for the expression of hrpG and prhG (Hikichi et al ., ; Zhang et al ., ), indicating that the regulation of PrhO on the expression of hrpG and prhG is independent of these known regulating pathways. Recently, we have identified a plant‐derived compound, umbelliferone, which impairs T3SS expression via HrpG and PrhG, but independent of these known regulators (Yang et al ., ), supporting our speculation that certain novel pathways should be integrated for the expression of hrpG and prhG in R. solanacearum . It should be noted that HrpB is not expressed until contact with hrp ‐inducing medium or with host plants, whereas HrpG is best expressed in rich medium.…”
Section: Discussionsupporting
confidence: 86%
“…It is worth noting that the best antimicrobial activities were also displayed by these same coumarins, raising the possibility that the biofilm suppression may simply reflect the limitation of growth under these conditions. The authors subsequently followed up this study with analysis of umbelliferone and its antivirulence activity against R. solanacearum (Yang et al 2017 ). The type three secretion system (T3SS) and biofilm formation were both suppressed.…”
Section: Coumarins As Anti-qs and Antibiofilm Agents Against Clinicalmentioning
confidence: 99%
“…Coumarins are a large family of naturally derived fused benzene and a-pyrone rings found primarily in a wide range of plant sources. Some coumarins are regarded as phytoalexins which are plant resistance compounds that are biosynthesised by plant tissues in response to pathogenic infection (Yang et al 2017 ). Members of the coumarin class of compound have also been identified in bacteria and fungi, such as novobiocin and coumermycin isolated from Streptomyces (Eustaquio et al 2003 ), and aflatoxins isolated from different Aspergillus species (Kumar et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…These greater rates of nutrient removal by the biofilm communities is assumed to be the result of the greater microbial biomass associated with this niche, relative to the planktonic communities. Though not determined during this study, biofilms have also been shown to support microbial groups with physiological capabilities for the metabolism of nutrients that are not associated with the planktonic communities ( Nadell et al, 2016 ; Stubbendieck et al, 2016 ; Jones and Bennett, 2017 ).…”
Section: Discussionmentioning
confidence: 89%